Monetary Policy, Inflation Rate, and Stock Market in Malaysia - Yeap, Sin Yean (2004)

(untitled)
The purpose of this study is to examine the relationship between monetary policy, inflation rate, and stock market in Malaysia. The techniques used in this study are Unit Root test, Johansen's Cointegration test, Pairwise Granges Causality test, Multivariate VAR tests, Impulse Response, Variance Decomposition and Multivariate Error Correction Model (ECM) tests. Five variables used in this study are exchange rate, lending rate, consumer price, and aggregate money supply. Data will be collected monthly and the data will be divided into two periods. The first period will be from January 1980 until August 1998 representing the period before the government pegged the exchange rate. The second period will start from September 1998 until September 2003 representing the period after the government had pegged the exchange rate. The major findings are : (i) there exist a dynamic interaction between monetary policy, inflation rate and stock market in Malaysia, and (ii) there is a linkage between the variables and stock market before and after the government had pegged the exchange rate.